THE IMPLEMENTATION OF CHARACTER EDUCATION THROUGH ISLAMIC EDUCATION LEARNING AT SMP PGRI I BOJONEGORO - su yati (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2017)
AbstractCharacter education is a process of transformation of life values to be developedin the personality of a person or student so it becomes one in the person’slife behavior. Character education is not only about teaching what is rightand what is wrong, more than that character education inculcate habits aboutgood so students become the wrong idea which one is right, and able to feelgood value so students will be able to do good things. This study is aimed toteach the characters values and analyze the obstacles and supporting factorsof the character education of students through Islamic Education learningin SMP PGRI I Bojonegoro. Qualitative research method is used in thisstudy, a research method that does not use the count (statistics) but throughdata collection, analysis and then interpretation. The qualitative descriptiveresearch attempts to describe the situation or events, does not seek or explainthe relationship but describes the situation. The research results show that thevalues taught to students of SMP PGRI 1 Bojonegoro are religious, honesty,democratic, social interest, environmental interest, discipline. The supportingfactors of the implementation of character education are the availability offacilities, and proper classroom infrastructure, good student learning interests,comfortable class atmosphere, and clean classroom. Keywords: Character Education, Islamic Education Subject